Deep-Sea Hydrothermal Vent Viruses Compensate for Microbial Metabolism in Virus-Host Interactions - Tianliang He (American Society for Microbiology, 2017)
ABSTRACT Viruses are believed to be responsible for the mortality of host organisms. However, some recent investigations reveal that viruses may be essential for host survival. To date, it remains unclear whether viruses are beneficial or harmful to their hosts. To reveal the roles of viruses in the virus-host interactions, viromes and microbiomes of sediment samples from three deep-sea hydrothermal vents were explored in this study. To exclude the influence of exogenous DNAs on viromes, the virus particles were purified with nuclease (DNase I and RNase A) treatments and cesium chloride density gradient centrifugation. The metagenomic analysis of viromes without exogenous DNA contamination and microbiomes of vent samples indicated that viruses had compensation effects on the metabolisms of their host microorganisms. Viral genes not only participated in most of the microbial metabolic pathways but also formed branched pathways in microbial metabolisms, including pyrimidine metabolism; alanine, aspartate, and glutamate metabolism; nitrogen metabolism and assimilation pathways of the two-component system; selenocompound metabolism; aminoacyl-tRNA biosynthesis; and amino sugar and nucleotide sugar metabolism. As is well known, deep-sea hydrothermal vent ecosystems exist in relatively isolated environments which are barely influenced by other ecosystems. The metabolic compensation of hosts mediated by viruses might represent a very important aspect of virus-host interactions. IMPORTANCE Viruses are the most abundant biological entities in the oceans and have very important roles in regulating microbial community structure and biogeochemical cycles. The relationship between virus and host microbes is broadly thought to be that of predator and prey. Viruses can lyse host cells to control microbial population sizes and affect community structures of hosts by killing specific microbes. However, viruses also influence their hosts through manipulation of bacterial metabolism. We found that viral genes not only participated in most microbial metabolic pathways but also formed branched pathways in microbial metabolisms. The metabolic compensation of hosts mediated by viruses may help hosts to adapt to extreme environments and may be essential for host survival.